Pengaruh CAR, ROA, NPM dan LDR terhadap Pertumbuhan Laba Bank - Ermaini Ermaini; Irmanelly Irmanelly (Universitas Muhammadiyah Jambi, 2014)
This research aims to estimates the effect of CAR, ROA, NPM and LDR to bank profit growth case study at PT. Bank Mandiri, Tbk in the period 2002.I-2009.IV. The data which is used are secondary data in the form of quarterly financial statements published by PT. Bank Mandiri, Tbk . This study uses ratio analysize and regression analysis. Variable of CAMEL are independent of the ratio Capital Adequacy Ratio(CAR), Return on Asset (ROA), Net Profit Margin (NPM) dan Loan to Deposit Ratio (LDR).While the variable dependent is profit growth. The results showed that only variable of NPM which has significant influence on the growth of banking profits.